1999
DOI: 10.1002/etc.5620180317
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of fish embryos to weathered crude oil: Part I. Low‐level exposure during incubation causes malformations, genetic damage, and mortality in larval pacific herring (Clupea pallasi)

Abstract: Pacific herring eggs were exposed for 16 d to weathered Alaska North Slope crude oil. Exposure to an initial aqueous concentration of 0.7 parts per billion (ppb) polynuclear aromatic hydrocarbons (PAHs) caused malformations, genetic damage, mortality, and decreased size and inhibited swimming. Total aqueous PAH concentrations as low as 0.4 ppb caused sublethal responses such as yolk sac edema and immaturity consistent with premature hatching. Responses to less weathered oil, which had relatively lower proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
90
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(100 citation statements)
references
References 28 publications
(64 reference statements)
8
90
1
1
Order By: Relevance
“…Field and laboratory investigations demonstrated that there was a common syndrome of crude oil-induced developmental toxicity in a range of teleost fish. This was described by pericardial edema, body axis curvature, yolk edema and jaw reductions (Heintz et al, 1999;Carls et al, 1999;Pollino and Holdway, 2002;Couillard, 2002). These results of the studies were in agreement with the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Field and laboratory investigations demonstrated that there was a common syndrome of crude oil-induced developmental toxicity in a range of teleost fish. This was described by pericardial edema, body axis curvature, yolk edema and jaw reductions (Heintz et al, 1999;Carls et al, 1999;Pollino and Holdway, 2002;Couillard, 2002). These results of the studies were in agreement with the current study.…”
Section: Discussionsupporting
confidence: 93%
“…However, it models exposure not to fresh oil but to stranded, weathered oil. The composition and concentrations of test solutions change over days and weeks as the more water‐soluble components are depleted (Carls et al ; Martin et al ) and when droplets are periodically released from oil films (J. Adams, unpublished data).…”
Section: Exposure Regimesmentioning
confidence: 99%
“…PAHs are known to be highly toxic to larval herring, topsmelt, minnow, and salmon (Petersen and Kristensen, 1998;Heintz et al, 1999;Couillard et al, 2005). Toxic effects include hemorrhages, spinal deformities, growth retardation, and death (Billiard et al, 1999;Carls et al, 1999 (Kujawinski et al, 2011). The use of subsurface dispersants combined with high pressure and turbulence at the wellhead likely contributed to the formation of the subsurface oil plumes that were unique to the DWH (Kujawinski et al, 2011).…”
Section: April 20 2010mentioning
confidence: 99%